Effect of thermal annealing on the optical stability of amorphous Ge–Se–Te films. (11th November 2020) - Chen, Jinbo; Qin, Jingshuang; Zhang, Limeng; Chen, Yimin; Shen, Xiang; Gu, Jierong; Xu, Tiefeng
Abstract: Ge–Se–Te chalcogenide films with Ge content from 10% to 27% were prepared using thermal evaporation. The films were annealed with different times, and the changes of the linear refractive index and optical band gap of the films with different chemical compositions were investigated. It was found that, after 30 h of annealing, the Ge20 Se8.5 Te71.5 film exhibits the smallest change ratio in terms of linear refractive index (<0.5%), optical band gap (<1.5%), and thickness (<2.5%). Therefore, this component has the best optical stability in the Ge–Se–Te system studied in this paper. The optical band gap of Ge20 Se8.5 Te71.5 is about 0.8 eV, and the refractive index exceeds 3.4, which is beneficial to the applications in Te-based optical waveguide devices.